On the ubiquitous presence of fractals and fractal concepts in pharmaceutical sciences: A review - Pippa, Natassa; Dokoumetzidis, Aristides; Costas Demetzos; Macheras, Panos (INTERNATIONAL JOURNAL OF PHARMACEUTICS, 2013)
Fractals have been very successful in quantifying nature's geometrical complexity, and have captured the imagination of scientific community. The development of fractal dimension and its applications have produced significant results across a wide variety of biomedical applications. This review deals with the application of fractals in pharmaceutical sciences and attempts to account the most important developments in the fields of pharmaceutical technology, especially of advanced Drug Delivery nano Systems and of biopharmaceutics and pharmacokinetics. Additionally, fractal kinetics, which has been applied to enzyme kinetics, drug metabolism and absorption, pharmacokinetics and pharmacodynamics are presented. This review also considers the potential benefits of using fractal analysis along with considerations of nonlinearity, scaling, and chaos as calibration tools to obtain information and more realistic description on different parts of pharmaceutical sciences. As a conclusion, the purpose of the present work is to highlight the presence of fractal geometry in almost all fields of pharmaceutical research. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Advanced Drug Delivery nano Systems (aDDnSs); Biopharmaceutics; Fractal analysis; Morphology; Nanotechnology; Pharmacokinetics